The Reality of Using Digital Platforms and their Impact on Achieving Social Solidarity, the (Ehsan) Platform as a Model - Abed, Fahad Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The research studies the reality of using digital platforms in the world in general, then in the Kingdom of Saudi Arabia in particular, with an emphasis on the role of the Saudi National Platform for Charitable Work (Ehsan) in achieving social solidarity. The research adopted the descriptive approach to show the reality of using digital platforms in the world and Saudi Arabia in particular, and then the analytical statistics of the Ehsan platform through its contribution to achieving social solidarity. The significance of the research is revealed by examining the concept of digital technologies and their global contribution to development and economic development, as well as the extent to which they are used in achieving the foundations and objectives of the Islamic economy via one of its pillars, social solidarity. The study emphasized the role of the Saudi National Platform for Charitable Work (Ehsan) in achieving social solidarity by integrating government agencies with the private and charitable sectors. This demonstrates the Kingdom of Saudi Arabia’s technological infrastructure’s strength. The research has proved the first hypothesis: that there is a clear effect of using digital platforms on achieving social solidarity. Also, the research has denied the second hypothesis: a significant correlation with the increase or decrease in the amounts of money status reported on the Ehsan platform, based on the community’s interest in covering it. This confirms the community’s solidarity with all cases through digital platforms. This confirms the solidarity of society with all humanitarian cases through digital platforms.